AB0805 Nailfold capillaroscopy findings are different between patients with U1RNP antibody and systemic sclerosis or patients with systemic lupus erythematosus and U1RNP antibody. (23rd January 2014) - Castellví, I.; Moya-Alvarado, P.; Sarmiento, M.; Geli, C.; Diaz-Torne, C.; Corica, M.E.; Laiz, A.; Casademont, J.; de Llobet, J.M.
Abstract : Background: Nailfold capillaroscopy (NC) is the best tool to study microcirculation in patients with Raynaud's phenomenon (RF) or patients with connective tissue diseases. There are some characteristic capillaroscopy findings in systemic sclerosis (SSc) patients, like presence of giant capillaries (GC) or loss of capillary density (LCD). Patients with Systemic Lupus Erythematosus (SLE) and RF may present nonspecific changes in the NC, but sometimes NC in SLE patient can simulate SSc findings. Anti-U1RNP antibodies may be present in both entities and are associated with a greater number of alterations in NC. Objectives: To Determine the existence of differences between the findings of nailfold capillaroscopy in patients with SSc or SLE that present U1RNP antibodies. Methods: Patients with SSc o earlySSc (eSSc) and positive determination of anti-U1RNP antibodies were included. Afterwards these patients were compared with a cohort of patients with SLE with anti-U1RNP antibodies. In both groups we studied in NC the following findings: presence o absence of giant capillaries (GC), angiogenesis and loss of capillary density (LCD). We compare findings with Chi-Square or Fisher's test when it was needed. Statistcial analysis were performed by SPSS program v17.0 Results: One hundred thirty-five SSc patients (93.4% women) and 76 SLE patients (94.7% women) were included. Determinatio of anti U1RNP abs were performed in 134 SSc patients and in 67 SLE patients. SLE patients had more U1RNP antibodies (10/134 [7.4%]) than SSc patients (13/67 [19.4%];p=0.012). NC showed GC, loss of capillary density and angiogenesis in 71.4%, 100% and 100% in SSc patients with U1RNP antibodies. SLE patients presented less pathological findings in NC that SSc patients (GC in 38.4%, LCD in 46.1% and angiogenesis in 69% of patients). A significant difference in NC between SSc and SLE patients were found in capillary density (lower in patients with SSc (p=0.04). Conclusions: AntiU1RNP antibody is find more frequently in SLE patients than in SSc patients. Patients with SSc and U1RNP have more loss of capillary density in NC than SLE patients. Presence or absence of Loss of capillary density in patients with undifferenciated connective tissue disease with anti-U1RNP, or patients classified as mixed connective tissue disease could be useful to predict witch patients will develop SSc or SLE. We need more studies to determinate the use of NC in patients with antiU1RNP antibodies. Disclosure of Interest: None Declared